2024
DOI: 10.1002/jsfa.13438
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing saltiness perception in bone broth: the additive effect of oil and optimization of sodium‐reduction formula for consumer acceptability

Lulu Zhang,
Xiaoxiao Cao,
Baoqing Zhu
et al.

Abstract: BackgroundExcessive NaCl intake in liquid and semi‐solid food (e.g., soup, hot pot base, sauce) poses a high risk to human health, and reducing NaCl intake is a major concern for global health.ResultsUsing the generalized Labeled Magnitude Scale (gLMS) method, the study verified the possibility of sodium reduction through oil addition. The compromised acceptance threshold (CAT) and hedonic rejection threshold (HRT) have been determined. The gLMS results showed that the saltiness intensity of samples containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Different kinds of food emulsions, including water-in-oil (W/O), oil-in-water (O/W), and water-in-oil-in-water (W/O/W) emulsions, can be used to create inhomogeneous salt concentration gradients in liquid foods. In O/W emulsions, higher oil content and lower water aqueous phase were perceived saltier and higher interfacial area helped to increase saltiness intensity. , Based on this concept, the combination of oil and NaCl content was optimized to enhance saltiness perception of bone broth with a salt reduction of around 20% . W/O/W has the advantages to encapsulate NaCl in the inner water phase, which have been more popular than O/W emulsions to control the saltiness perception. It was reported that the application of a W/O/W emulsion salt-containing system stabilized with nonchemically modified glutinous rice starch could reduce salt in tomato soup by 25% .…”
Section: Introductionmentioning
confidence: 99%
“…Different kinds of food emulsions, including water-in-oil (W/O), oil-in-water (O/W), and water-in-oil-in-water (W/O/W) emulsions, can be used to create inhomogeneous salt concentration gradients in liquid foods. In O/W emulsions, higher oil content and lower water aqueous phase were perceived saltier and higher interfacial area helped to increase saltiness intensity. , Based on this concept, the combination of oil and NaCl content was optimized to enhance saltiness perception of bone broth with a salt reduction of around 20% . W/O/W has the advantages to encapsulate NaCl in the inner water phase, which have been more popular than O/W emulsions to control the saltiness perception. It was reported that the application of a W/O/W emulsion salt-containing system stabilized with nonchemically modified glutinous rice starch could reduce salt in tomato soup by 25% .…”
Section: Introductionmentioning
confidence: 99%